Aplikasi Distribusi Buku Di Unit Pelaksana Teknis (UPT) Dinas Pendidikan Kecamatan Sambirejo Kabupaten Sragen - Laraswati Wahyu Priyono, Muhammad Hasbi, Sri Tomo (Jurnal Ilmiah SINUS, 2013)
Application monitoring the distribution of the book is one application that can be used for the processing of data about books. Monitoring textbooks in the Technical Implementation Unit Sambirejo the District Education Office has not so the maximum, so that such problems arise in the form of doing a special data processing in the data perekapan book, ineffective distribution of books in every school.The purpose of this research is to design and build applications in the Book Distribution Unit of the Technical Education Department in the distribution of books in each school in the district Sambirejo Sragen. With 27 elementary schools and a number of 7 types textbooks such as Indonesian, Mathematics, Natural Sciences, Social Sciences, Education Citizenship, English. With this application is expected to provide ease of deployment of the book at each school. The data collection method that the authors use include field studies and literature. Field studies conducted with frequently asked questions or interview and observation or observation. In terms of programming language the author uses language program Hyper Text Preprocessor (PHP). Keywords : book, monitoring, Technical Education Department, school